Abundance of ruminal bacteria, epithelial gene expression, and systemic biomarkers of metabolism and inflammation are altered during the peripartal period in dairy cows - Minuti, A. (2015)
Seven multiparous Holstein cows with a ruminal fistula were used to investigate the changes in rumen microbiota, gene expression of the ruminal epithelium, and blood biomarkers of metabolism and inflammation during the transition period. Samples of ruminal digesta, biopsies of ruminal epithelium, and blood were obtained during −14 through 28 d in milk (DIM). A total of 35 genes associated with metabolism, transport, inflammation, and signaling were evaluated by quantitative reverse transcription-PCR. Among metabolic-related genes, expression of HMGCS2 increased gradually from −14 to a peak at 28 DIM, underscoring its central role in epithelial ketogenesis. The decrease of glucose and the increase of nonesterified fatty acids and β-hydroxybutyrate in the blood after calving confirmed the state of negative energy balance. Similarly, increases in bilirubin and decreases in albumin concentrations after calving were indicative of alterations in liver function and inflammation. Despite those systemic signs, lower postpartal expression of TLR2, TLR4, CD45, and NFKB1 indicated the absence of inflammation within the epithelium. Alternatively, these could reflect an adaptation to react against inducers of the immune system arising in the rumen (e.g., bacterial endotoxins). The downregulation of RXRA, INSR, and RPS6KB1 between −14 and 10 DIM indicated a possible increase in insulin resistance. However, the upregulation of IRS1 during the same time frame could serve to restore sensitivity to insulin of the epithelium as a way to preserve its proliferative capacity. The upregulation of TGFB1 from −14 and 10 DIM coupled with upregulation of both EGFR and EREG from 10 to 28 DIM indicated the existence of 2 waves of epithelial proliferation. However, the downregulation of TGFBR1 from −14 through 28 DIM indicated some degree of cell proliferation arrest. The downregulation of OCLN and TJP1 from −14 to 10 DIM indicated a loss of tight-junction integrity. The gradual upregulation of membrane transporters MCT1 and UTB to peak levels at 28 DIM reflected the higher intake and fermentability of the lactation diet. In addition, those changes in the diet after calving resulted in an increase of butyrate and a decrease of ruminal pH and acetate, which partly explain the increase of Anaerovibrio lipolytica, Prevotella bryantii, and Megasphaera elsdenii and the decrease of fibrolytic bacteria (Fibrobacter succinogenes, Butyrivibrio proteoclasticus). Overall, these multitier changes revealed important features associated with the transition into lactation. Alterations in ruminal epithelium gene expression could be driven by nutrient intake–induced changes in microbes; microbial metabolism; and the systemic metabolic, hormonal, and immune changes. Understanding causes and mechanisms driving the interaction among ruminal bacteria and host immunometabolic responses merits further study.